The role of financial factors in the mobility and location choices of General Practitioners in Australia - Michelle McIsaac; Anthony Scott; Guyonne Kalb (BMC, 2019)
Abstract Background The geographic distribution of health workers is a pervasive policy concern. Many governments are responding by introducing financial incentives to attract health care workers to locate in areas that are underserved. However, clear evidence of the effectiveness of such financial incentives is lacking. Methods This paper examines General Practitioners' (GPs) relocation choices in Australia and proposes a dynamic location choice model accounting for both source and destination factors associated with a choice to relocate, thereby accounting for push and pull factors associated with job separation. The model is used to simulate financial incentive policies and assess potential for such policies to redistribute GPs. This paper examines the role of financial factors in relocating established GPs into neighbourhoods with relatively low socioeconomic status. The paper uses a discrete choice model and panel data on GPs' actual changes in location from one year to the next. Results This paper finds that established GPs are not very mobile, even when a financial incentive is offered. Policy simulation predicts that 93.2% of GPs would remain at their current practice and that an additional 0.8% would be retained or would relocate in a low-socioeconomic status (SES) neighbourhood in response to a hypothetical financial incentive of a 10% increase in the earnings of all metropolitan GPs practising in low-SES neighbourhoods. Conclusion With current evidence on the effectiveness of redistribution programmes limited to newly entering GPs, the policy simulations in this paper provide an insight into the potential effectiveness of financial incentives as a redistribution policy targeting the entire GP population. Overall, the results suggest that financial considerations are part of many factors influencing the location choice of GPs. For instance, GP practice ownership played almost as important a role in mobility as earnings.